When High-Capacity Readers Slow Down and Low-Capacity Readers Speed Up: Working Memory and Locality Effects - Nicenboim, Bruno; Logačev, Pavel; Gattei, Carolina; Vasishth, Shravan (Frontiers in Psychology, 2016)
We examined the effects of argument-head distance in SVO and SOV languages (Spanish and German), while taking into account readers’ working memory capacity and controlling for expectation (Levy, 2008) and other factors. We predicted only locality effects, that is, a slow-down produced by increased dependency distance (Gibson, 2000; Lewis & Vasishth, 2005). Furthermore, we expected stronger locality effects for readers with low working memory capacity. Contrary to our predictions, low-capacity readers showed faster reading with increased distance, while high-capacity readers showed locality effects. We suggest that while the locality effects are compatible with memory-based explanations, the speedup of low-capacity readers can be explained by an increased probability of retrieval failure. We present a computational model based on ACT-R built under the previous assumptions, which is able to give a qualitative account for the present data and can be tested in future research. Our results suggest that in some cases, interpreting longer RTs as indexing increased processing difficulty and shorter RTs as facilitation may be too simplistic: The same increase in processing difficulty may lead to slowdowns in high-capacity readers and speedups in low-capacity ones. Ignoring individual level capacity differences when investigating locality effects may lead to misleading conclusions.